Effect of Online Modules on Pre-Service Teacher Mental Health Literacy and Efficacy toward Inclusive Practices - Gilham, Chris; Neville-MacLean, Sherry; Atkinson, Emily (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Mental health literacy (MHL) for pre-service teachers seeks to improve knowledge and help-seeking behaviours and decrease stigma. Increased MHL may also change perceived stress and self-efficacy for inclusive practices. This cohort study evaluates the impact of an online MHL resource for educators, embedded within a mandatory Bachelor of Education (BEd) course, on pre-service teachers’ MHL, perceived stress, and teacher efficacy toward inclusive practices. Seventy-one pre-service teachers completed the course as well as pre- and post-surveys. Results demonstrated significant and substantial improvements on knowledge, help-seeking, and perceived efficacy for inclusive practices. Increased MHL may be an effective approach in meeting the requirements of inclusive education.